1998
DOI: 10.1016/s0160-2896(99)80057-9
|View full text |Cite
|
Sign up to set email alerts
|

From good senses to good sense: A link between tactile information processing and intelligence

Abstract: Since the 1970s there has been an reemerging interest in Galton's (1883) senses-intelligence hypothesis. The essence of this hypothesis is the conceptual link between fine-tuned sensory functioning and superior intellectual ability. Several studies have investigated the sensory-cognitive link within auditory and visual modalities. In this study, the intersystemic relationship between sensory and cognitive functioning was extended to the tactile modality by examining the associations between three measures of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
28
0
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 56 publications
(33 citation statements)
references
References 68 publications
4
28
0
1
Order By: Relevance
“…Our use of a diverse test battery with a sample that was over 15 times the size of the latter undergraduate sample, however, may yield more precise point estimates than in previous studies. The above findings on pitch discrimination, combined with our finding of an age-partialled correlation of .31 between g and a test of color discrimination and with other investigators' findings of age-partialled correlations of .23 and .31 between g and two tests of tactile discrimination (Li et al, 1998), form a consistent network of modest associations between sensory discrimination and general intelligence.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our use of a diverse test battery with a sample that was over 15 times the size of the latter undergraduate sample, however, may yield more precise point estimates than in previous studies. The above findings on pitch discrimination, combined with our finding of an age-partialled correlation of .31 between g and a test of color discrimination and with other investigators' findings of age-partialled correlations of .23 and .31 between g and two tests of tactile discrimination (Li et al, 1998), form a consistent network of modest associations between sensory discrimination and general intelligence.…”
Section: Discussionsupporting
confidence: 89%
“…Deary (1994a), Deary, Caryl, Egan, and Wight (1989), and Deary, Head, and Egan (1989), by contrast, have sided with Cattell, claiming that the correlation between AIT and intelligence is separable from the relation of AIT to pitch discrimination. Both the Spearman and Cattell explanations suggest an important role for elementary information processing in explaining g; the Spearman explanation, however, rules out the possibility of a negligible relation between measures of sensory discrimination and g. Despite one study of tactile discrimination that found evidence for weak associations with g (Li, Jordanova, & Lindenberger, 1998), these hypotheses have up to now been tested primarily in the auditory modality using only small samples.…”
Section: Introductionmentioning
confidence: 99%
“…Both our LGM and DCSM results demonstrate that correlations among intellectual and sensory Level components are high, and do not primarily reflect shared mean age trends; when controlling for age at initial testing, these correlations continued to be substantial and statistically reliable. This finding confirms and extends evidence based on cross-sectional analyses of the present and comparable samples (Anstey et al, , 1993Anstey & Smith, 1999;Anstey, 1999b;Clement, 1974;Li et al, 1998;Lindenberger & Baltes, 1994;Rabbitt, 1991;Roberts et al, 1997;Schaie, 1996;Salthouse et al, 1996Salthouse et al, , 1998Stankov, 1986;Stankov & Anstey, 1997;Stankov, Seizova-Cajić, & Roberts, 2001). In old and very old age, intellectual and sensory domains of functioning are closely related (e.g., Clark, 1960;Cohn, Dustman, & Bradford, 1984;Dirken, 1972;Heron & Chown, 1967;Lindenberger & Baltes, 1994;Welford & Birren, 1965).…”
Section: Discussionsupporting
confidence: 88%
“…Even in a much younger sample and with a more restricted age range (i.e. age range from 30 to 50 years), Li et al [32] also found that elementary tactile information processing predicts individual differences in intelligence.…”
Section: Scope Of the Current Studymentioning
confidence: 99%